Who Do We Learn from at Work? Interlinked Communities of Practice and Informal Learning - David Boud; Heather Middleton (Adult Education Research Conference, 2002)
This paper addresses the question of who is involved in learning in workplaces. It draws on a study of multiple worksites with differentiated work within a large educational organization. It discusses the value of communities of learning in conceptualizing the question and suggests that additional factors such as social networks, structural relationships and the context of particular work need to be considered.